Pemanfaatan Asterisk Pada Voice Over Internet Protocol (Voip) - Sony Oktapriandi (MANAJEMEN INFORMATIKA, 2009)
Growth of world technology of information grow rapidly. For example today us newly recognize the technology of concerning computer network, day after have there is again new technology which emerge. One of fast information technology evidence progressively its growth iswe can communicate through internet medium. The Technology name is] VOIP (Voice Over Internet Protocol). With the existence of the technology, we can communicate through internet media with the friend which far its place without thinking what is the cost. Because expense communicate with it are cheap. Writer try the information technology simulation into final duty writing. By using classic method Called a structure Analysis (Pressman, 2002). Consisted of the problem recognition, evaluate and sintesis, model, Specification, and study. The information technology Simulation use the operating system of Linux and use the software Asterisk.